Characterization of Gammaherpesvirus 68 Gene 50 Transcription - Liu, Shaofan (American Society for Microbiology, 2000)
Gene 50 is the only immediate-early gene that appears to be conserved among the characterized gammaherpesviruses. It has recently been demonstrated for the human viruses Epstein-Barr virus (EBV) and Kaposi's sarcoma-associated herpesvirus (KSHV) that ectopic expression of the gene 50-encoded product in some latently infected cell lines can lead to the induction of virus replication, indicating that gene 50 is likely to play a pivotal role in regulating gammaherpesvirus reactivation. Here we demonstrate that the murine gammaherpesvirus 68 (γHV68) gene 50 is an immediate-early gene and that transcription of γHV68 gene 50 leads to the production of both spliced and unspliced forms of the gene 50 transcript. Splicing of the transcript near the 5′ end serves to extend the gene 50 open reading frame, as has been observed for the gene 50 transcripts encoded by KSHV and herpesvirus saimiri (Whitehouse et al., J. Virol. 71:2550–2554, 1997; Lukac et al., Virology 252:304–312, 1998; Sun et al., Proc. Natl. Acad. Sci. USA 95:10866–10871, 1998). Reverse transcription-PCR analyses, coupled with S1 nuclease protection assays, provided evidence that gene 50 transcripts initiate at several sites within the region from bp 66468 to 66502 in the γHV68 genome. Functional characterization of the region upstream of the putative gene 50 transcription initiation site demonstrated orientation-dependent promoter activity and identified a 110-bp region (bp 66442 to 66552) encoding the putative gene 50 promoter. Finally, we demonstrate that the γHV68 gene 50 can transactivate the γHV68 gene 57 promoter, a known early gene target of the gene 50-encoded transactivator in other gammaherpesviruses. These studies show that the γHV68 gene 50 shares several important molecular similarities with the gene 50 homologs in other gammaherpesviruses and thus provides an impetus for future studies analyzing the role of the γHV68 gene 50-encoded protein in acute virus replication and reactivation from latency in vivo.